Gas emission on the poultry production - Sousa, F.C. (2017)
Among the greenhouse gases produced in broiler chicken production environments, ammonia stands out for being present in higher concentrations and for significantly affecting human and animal health. Thus, this review evaluates the various sources of ammonia generation in animal production facilities, the damages caused by ammonia emissions in broiler chicken production facilities, and the accompanying economic losses. The main source of ammonia in broiler production is the nitrogen ingested in the diet, which is broken down into uric acid and, eventually, into ammonia that is volatilized from the bed to the environment. High ammonia concentrations in such facilities can affect productivity and result in economic losses. The effects on the environment are eutrophication of water bodies and ground water contamination. Ammonia emission control in poultry production facilities is therefore inevitable to avoid economic losses, prevent environmental damage, and increase feed efficiency.